Performance analysis of a wireless communication network using MIMO system - Saha, Siddharth; Shajib, Kamrul Hasan; Saha, Archita (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.